LaseiRon - Mohamad Zain, Muhammad Asyraf; Rujhan, Khairul Iffan; Mohd Ahyad, Mohamad Nur Adam; Ahmad Daud, Muhamad Ghulwani (2019)
Ironing clothes is a common activity in our daily life. When we want to go to work or school or any event, we have to iron the cloth to be more dashing or beautiful. Each ironing takes a lot of time to complete iron. For ironing cloth many people still used traditional iron or maybe steam iron but it still taking a lot of times. So laseiRon is introduce to overcome this problem. The laseiRon is simpler to use and short the time in ironing that usually traditional iron taken. The laseiRon is included with laser to help the consumer to ironing more than one cloth at a time. The heat of the laser will be set according to type cloth. The level of heat can be chosen at the laseiRon monitor. It also included with sensor to sensor the existence of cloth, the laseiRon will start when there is cloth at the area of rod. The sensor also is used to sensor if the cloth has completed ironing or not. This sensor is used to make sure the safety of consumer and to prevent burning to happen